Arrangements for Taking Minuta of Deeds Made Based on False Statements in Criminal Trials - Dirgantara, Pebry; Kasih, Desak Putu Dewi; Jayantiari, I Gusti Agung Mas Rwa; Dananjaya, Nyoman Satyayudha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research addresses legal issues related to the use of deed minutes as evidence in criminal cases involving false statements made by a notary. According to Article 66 paragraph (1) of Law No. 2 of 2014 and Article 23 paragraph (1) of the Regulation of the Minister of Law and Human Rights No. 7 of 2016, discrepancies arise regarding the admissibility of deed minutes in judicial processes when false information is provided. The research examines the regulations for using deed minutes as evidence in criminal justice cases involving falsified statements by a notary and explores the legal status and consequences of deed minutes when proven to contain falsified information.